Preparo do Cacau: Pesquizas Feitas Desde 1900 com o Fim de Modificar e Melhorar a sua Technica - PortÃ¨res, M. (REVISTA DE AGRICULTURA, 2017)
Preparo do Cacau: Pesquizas Feitas Desde 1900 com o Fim de Modificar e Melhorar a sua Technica